COMPARATIVE TREATMENT REGARDING THE LEGAL CLASSIFICATION OF ACTS THAT AFFECT THE SEXUAL LIFE OF MINORS - CIOBANU , Tudor Cristian (International Journal of Legal and Social Order, 2022)
This article aims to carry out an analysis of the different methods of regulating offences against sexual self-determination, especially in relation to minors. From this comparative view will result the different views on this aspect of the European legislators in Germany and France, for example regarding the value of the consent of a minor victim of such crimes. This approach can be useful for a better understanding of the optimal way to legislatively counter this criminal phenomenon, namely what changes could be made in the national legislation in this regard. Also, this analysis can even provide certain criteria to be considered by the magistrates when they establish the gravity of the offence. At present, this theme is of greatinterest,given that some opinions claim that the current legislation in Romania should be modified, for example because according to the current situation, a minor under 14 years old can consent to a sexual act.